Analysis of Customer Satisfaction Through Service Quality and Digital Payment in the Hermes Palace Hotel Medan - Steven Alfando; Sri Rezeki; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
This research is motivated by a decrease in customer satisfaction where it can be seen from the level of visitors every year has decreased due to the services provided to consumers being less than satisfactory and payments made can only use cash and debit/credit, resulting in a decrease in customer satisfaction which has an effect on the level of visitors without the hotel realizing it. The purpose of this study aims specifically to analyze Customer Satisfaction through Service Quality and Digital Payment in the Tourism Industry. The method used in this research is a quantitative method using primary data sources. Information will be analyzed by quantitative descriptive analysis obtained using a questionnaire instrument distributed to respondents and this research is measured using a Likert scale to obtain conclusions. The sampling technique used the Accidental Sampling technique. Then the data collected relating to the object is analyzed based on the respondents' responses obtained using the Slovin formula. Three hypotheses in this study were formulated and tested using multiple linear regression analysis. The results show that service quality and digital payment have a significant influence on customer satisfaction